2002
DOI: 10.1029/2001gl014071
|View full text |Cite
|
Sign up to set email alerts
|

Ocean color variability in the Tasman Sea

Abstract: The Tasman Sea contains the largest noncoastal surface chlorophyll‐a concentrations within the South Pacific Ocean. Observations of ocean color from SeaWiFS demonstrate that the chlorophyll‐a seasonal cycle is characterized by a large austral spring bloom and a much smaller fall bloom separated by periods of lower concentrations, typical of communities within the North Atlantic Ocean. However, the seasonal cycle of the mixed layer depth of the Tasman Sea is much more similar to the North Pacific Ocean, whose p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 7 publications
(6 reference statements)
0
47
1
Order By: Relevance
“…10 left panel), coccolithophores grew negligibly in nAtl and chl-a decreased in the two southern regions by different rates; total chl-a increased in all regions; PIC decreased strongly in nAtl and sAtl, while it strongly increased in sPac. This may have been caused by the strong SST-rise in the Tasman Sea (Tilburg et al, 2002), even though this SST rise was not observed in our sPac simple trend; however, the decreasing rate of SST in sAtl and sPac was clearly followed consistently by the decrease of coccolithophores; and the rate of increase of SST in nAtl was associated, at a small rate, with the increase of coccolithophores. The surface wind-speed decreased in nAtl is dominated by diatoms and the Weddell Sea has abundant coccolithophores, there are other studies (e.g.…”
Section: Interconnections Between Biological and Geophysical Parametersmentioning
confidence: 64%
See 3 more Smart Citations
“…10 left panel), coccolithophores grew negligibly in nAtl and chl-a decreased in the two southern regions by different rates; total chl-a increased in all regions; PIC decreased strongly in nAtl and sAtl, while it strongly increased in sPac. This may have been caused by the strong SST-rise in the Tasman Sea (Tilburg et al, 2002), even though this SST rise was not observed in our sPac simple trend; however, the decreasing rate of SST in sAtl and sPac was clearly followed consistently by the decrease of coccolithophores; and the rate of increase of SST in nAtl was associated, at a small rate, with the increase of coccolithophores. The surface wind-speed decreased in nAtl is dominated by diatoms and the Weddell Sea has abundant coccolithophores, there are other studies (e.g.…”
Section: Interconnections Between Biological and Geophysical Parametersmentioning
confidence: 64%
“…Moreover, large eddies occurring in the Tasman Sea have a great contribution to the vertical mixing within the upper ocean. This increased mixing effectively counteracts the winter stratification and results in a varying chl-a seasonal cycle (Tilburg et al, 2002). In this sense, the seasonal cycle of chl-a in sPac should be pronounced, similar to the North Atlantic, which has very strong mixing.…”
Section: Time Series Of Biological and Geophysical Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…This variation can also be applied to estimate absolute variations in the surface layer depth [81,82]. The correlation between SSH and thermocline depth is decreased by dipper and more diffuse thermocline and powerful surface buoyancy fluxes.…”
Section: Sea Surface Heightmentioning
confidence: 99%